How The Waste Land furthers an understanding of sustainable property management - Brown, Alistair (Emerald, 2019)
Purpose – Using the theory of sensibility, the purpose of this paper is to analyze how T.S. Eliot’s The Waste Land furthers our understanding of sustainable property management. Design/methodology/approach – Inter-connected indicators of environmental performance disclosures (EPD) and epistemological-based aesthetic environmental accounts (EBAEA) are used to textually analyze The Waste Land’s heightening of sustainable property management. Findings – The results of the study show that the level of EPD of The Waste Land was 80 per cent, while the level of The Waste Land’s EBAEA was 100 per cent. In terms of sustainable property management, the images of sustainable property management that permeate The Waste Land furthers our understanding of the apprehension of urban living, the intensification of assets and materials, the intrusiveness of city landmarks, the ephemeralness of the profit and loss, the inconstancy of water and the tension of torrid landscapes. Research limitations/implications – A research implication arising from the results of the study is that the property-poetry nexus may actualize new possibilities for discerning and imagining sustainable property management. Practical implications – The results of the study offer fruitful paths for understanding sustainability endeavour for planners, property managers, valuers, occupiers, accountants and developers. Social implications – TheWaste Land’s complex, multi-vocal, figurative, seemingly ambiguous lines render a sophisticated form of sustainable property scholarship that shapes aesthetic environmental accounts. Originality/value – The study’s originality rests in its methodological approach to identify, interpret and understand sustainable property management in a modernist poem. Keywords Environmental performance disclosures, Epistemological-based aesthetic environmental accounts, Sustainable property management